Traumatic Brain Injury in Qatar: Age Matters—Insights from a 4-Year Observational Study - Moamena El-Matbouly; Ayman El-Menyar; Hassan Al-Thani; Mazin Tuma; Hany El-Hennawy; Husham AbdulRahman; Ashok Parchani; Ruben Peralta; Mohammad Asim; Ahmed El-Faramawy; Ahmad Zarour; Rifat Latifi (The Scientific World Journal)
Background. Overall traumatic brain injury (TBI) incidence and related death rates vary across different age groups. Objectives. To evaluate the incidence, causes, and outcome of TBI in adolescents and young adult population in Qatar. Method. This was a retrospective review of all TBIs admitted to the trauma center between January 2008 and December 2011. Demographics, mechanism of injury, morbidity, and mortality were analyzed in different age groups. Results. A total of 1665 patients with TBI were admitted; the majority were males (92%) with a mean age of 28 ± 16 years. The common mechanism of injury was motor vehicle crashes and falls from height (51% and 35%, resp.). TBI was incidentally higher in young adults (34%) and middle age group (21%). The most frequent injuries were contusion (40%), subarachnoid (25%), subdural (24%), and epidural hemorrhage (18%). The mortality rate was 11% among TBI patients. Mortality rates were 8% and 12% among adolescents and young adults, respectively. The highest mortality rate was observed in elderly patients (35%). Head AIS, ISS, and age were independent predictors for mortality. Conclusion. Adolescents and adults sustain significant portions of TBI, whereas mortality is much higher in the older group. Public awareness and injury prevention campaigns should target young population.